Pengaruh Kepemimpinan Kepala Sekolah Terhadap Disiplin Kerja Guru IPS SMA Negeri 3 Kota Ternate - Irwan Abdullah (Jayapangus Press, 2019)
Principal leadership is an attitude carried out by the principal which includes actions to influence and direct the teacher in improving the effective learning process at school. Teacher's Work Discipline is a form of obedience to the behavior of a teacher in complying with the rules and provisions that have to do with activities in the school. The objectives of this study are: to determine the effect of principals' leadership on the work discipline of social studies teachers in Ternate 3 Public High School, while the research method used in research uses survey types or quantative research methods with steps or stages in the form of pre-field and field stages. Based on the results of statistical analysis using the product moment correlation formula and to test the significance of the correlation (r) obtained, it must be consulted first with the values ​​of (r) prodect-moment. Therefore, the degree of freedom (db) must be determined first, namely by the formula: db = N-1 thus db = 9 - 1 = 8. Based on the statistical test, it is obtained that r count is greater than r table, that is 0.75> 0.666 means that based on empirical data as a result of testing in the field there is a positive and significant relationship, it is estimated that the leadership of the principal has a relationship or influence on the work discipline of social studies teachers Ternate City. Thus it can be estimated that if the leadership of the school leader gets better, the better the discipline of working teachers in schools, and vice versa.